Biological removal of 17b-estradiol (e2) and 17a-ethinylestradiol (ee2) in a submerged membrane bioreactor using nitrifier-enriched inoculum - Patacasil, Liza B. (2012)
The continuous biological removal of 17b-Estradiol (E2) and 17a-Ethynylestradiol (EE2) in submerged membrane reactor (SMBR) was investigated in this study. Batch experiments were conducted in parallel with SMBR operation in order to gain understanding on the nature of removal of E2 and EE2. The rates of degradation of E2 and EE2 were determined using unacclimatized activated sludge and SMBR-grown and acllimatized sludge. Results achieved from batch experiments revealed that acclimatized SMBR sludge degrades E2 more that four times faster that AS sludge with first-order kinetic rate constants of 5.97 h-1 and 1.25 h-1, respectively. The rate of EE2 removal in batch mode using acclimatized sludge from SMBR was seven times faster than using unacclimatized AS sludge. The kinetic rate constants obtained for EE2 removal are 7.00 d-1 and 1.07 d-1 for SMBR and AS sludge, respectively. the k values for the degradation of E2 and EE2 proves that E2 is more degradable than EE2. Nitrification did not significantly affect the extent of biological removal of E2 but has shown to greatly enhance the rate of removal of EE2. The k value increased from 0.72 d-1 with ammonium monooxygenase (AMO) inhibition by allythiourea (ATU) to a k value of 7.00 d-1 without inhibition by ATU. The biological removal of EE2 is found to be influenced by operational parameters such as pH, MLSS and initial ammonium concentration. Complete removal of EE2 was achieved at pH 7.0 while higher initial ammonium concentration and higher MLSS concentration show faster rate of EE2 degradation. Batch sorption studies show that EE2 has greater tendency to sorb particulate solids than E2. Thermodynamic studies revealed that sorption process for both E2 and EE2 were exothermic, spontaneous, enthalpy-driven, and entropy-retarded. It was found that E removal is predominantly due to biodegradation while the nature of removal for EE2 is combined sorption and biodegradation. Complete removal of 24 -48 ug/gMLSS .d E@ was achieved during the continuous operation of SMBR at SRT of 10d and HRT of 10d. Continuous removal of EE2 in SMBR operating at SRT of 20dis found to be influenced by varying HRT (17h, 10h and 4h). Complete EE2 removal was achieved at HRT of 17h while % EE2 removal dropped to 53% and 42% when HRT was shortened to 10h and 4h, respectively.